L’emploi de formes d’adresse dans les interactions interculturelles – perceptions et discussions authentiques entre francophones et finnophones - Johanna Isosävi (Discours)
Politeness forms an integral part of communication, although the different frames of expectations can cause problems to L2 speakers. This article employs an intercultural approach and examines the uses of address forms (address pronouns T, V and the titles Monsieur, Madame and Mademoiselle) in interactions with Finnish and French speakers. The study combines an analysis of perceptions (focus groups) and production (authentic discussions), adopting relational work as the theoretical framework and relying on a discourse analysis of dialogues. The analysis shows that Finnish participants have difficulties with marked address forms, which they do not use much in their mother tongue, whereas for French participants, the non-utilisation of acquired forms seems unproblematic. Among Finnish participants, they fear a negative face will be attributed to them if they do not use “polite” address forms, but the reported evaluations from French speakers were not negative. Participants co-construct their experiences through discursive means, and their narratives often show shared knowledge. Finally, L2 speakers are not passive recipients, but exercise their agency by refusing an address form or suggesting an alternative. This study illustrates the advantages of living within a target language culture to increase one’s awareness of the uses of address forms and their variations.